2009
DOI: 10.1007/s12149-009-0255-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of 18F-2-deoxy-2-fluoro-glucose accumulation in the stomach on positron emission tomography

Abstract: Accumulation of (18)FDG in the stomach suggests a high probability of the presence of inflammatory change in the gastric mucosa forming a background for the development of cancer or malignant lymphoma, and thus requires further endoscopic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…They concluded that elevated esophagogastric FDG uptake does not predict cancer development and should not be investigated further if CT shows no unusual features. Takahashi et al [5] reported the association between the endoscopic view, Helicobacter pylori infection, and FDG accumulation in 272 patients who underwent a PET examination during a health check-up. They found FDG accumulation in 81 cases (30%), which they classified according to the following 2 patterns: (a) localized accumulation only in the fornix (Group A, n = 32) and (b) diffused accumulation throughout the stomach (Group B, n = 49).…”
Section: Physiological Fdg Uptake In Gastric Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that elevated esophagogastric FDG uptake does not predict cancer development and should not be investigated further if CT shows no unusual features. Takahashi et al [5] reported the association between the endoscopic view, Helicobacter pylori infection, and FDG accumulation in 272 patients who underwent a PET examination during a health check-up. They found FDG accumulation in 81 cases (30%), which they classified according to the following 2 patterns: (a) localized accumulation only in the fornix (Group A, n = 32) and (b) diffused accumulation throughout the stomach (Group B, n = 49).…”
Section: Physiological Fdg Uptake In Gastric Mucosamentioning
confidence: 99%
“…For gastric cancer screening, the usefulness of PET is limited because of physiological FDG uptake in the normal gastric wall and differences of FDG uptake according to the histological type of the tumor [1,2]. Physiological FDG deposits in the stomach may increase false-positive findings, although these deposits can be decreased by expanding the gastric wall by the patient consuming water or milk just before imaging acquisition [4,5]. As Koga et al [2] have reported, physiological gastric FDG uptake was shown to be significantly higher at the oral end; thus, strong gastric FDG uptake at the anal end suggested pathological uptake.…”
Section: Efficacy Of Pet For the Screening Of Gastric Cancermentioning
confidence: 99%
“…The same is true for the remnant stomach in subtotal gastrectomy patients [8]. Accumulation of F-18 FDG in the gastrointestinal smooth muscle due to accelerated gastric peristalsis or inflammatory changes have been suggested as possible causes for physiological and diffuse F-18 FDG uptake in the remnant stomach [23]. Also, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the mechanism is not clear. Several studies suggested that specific or non-specific gastritis is one of the causes of diffuse F-18 FDG uptake in the stomach, and these findings have a positive relationship with Helicobacter pylori infection [23,24]. Yun et al [8] reported that gastric distension due to ingestion of a glass of water is an effective way to diagnose in a patient with suspected gastric tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation